Safety at work - Ridley, John R. (Butterworth-Heinemann, 1990)
Safety at Work features articles from 25 specialist contributors written in association with the Institution of Occupational Safety and Health. This third edition of the book contains revisions to reflect developments in health and safety legislation and to rationalize the structure of some of the chapters.